2011
DOI: 10.1088/0004-637x/732/2/68
|View full text |Cite
|
Sign up to set email alerts
|

Colder and Hotter: Interferometric Imaging of Β Cassiopeiae and Α Leonis

Abstract: Near-infrared interferometers have recently imaged a number of rapidly rotating A-type stars, finding levels of gravity darkening inconsistent with theoretical expectations. Here, we present new imaging of both a cooler star β Cas (F2IV) and a hotter one α Leo (B7V) using the CHARA array and the MIRC instrument at the H band. Adopting a solid-body rotation model with a simple gravity darkening prescription, we modeled the stellar geometric properties and surface temperature distributions, confirming both stars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
117
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 43 publications
18
117
2
Order By: Relevance
“…This lower value is consistent with trends toward a lower expected value for a star with lower surface temperature (see Fig. 9 of Che et al 2011, andClaret 2000), although it is not nearly as small as would be expected for a fully radiative photosphere (β = 0.08).…”
Section: β Cas (Caph)supporting
confidence: 84%
See 2 more Smart Citations
“…This lower value is consistent with trends toward a lower expected value for a star with lower surface temperature (see Fig. 9 of Che et al 2011, andClaret 2000), although it is not nearly as small as would be expected for a fully radiative photosphere (β = 0.08).…”
Section: β Cas (Caph)supporting
confidence: 84%
“…Also as with Altair, Regulus has now been imaged by CHARA-MIRC Che et al (2011) (Table 1), but further rich detail has been added from the imaging. In particular, a much tighter constraint on inclination is now available (i = 7 In addition to its close companion, Regulus has a wide companion α Leo B at a separation of ∼175 , also a binary.…”
Section: The Resulting Solution Set For Regulus Is a Rather Rich Charmentioning
confidence: 99%
See 1 more Smart Citation
“…By using interferometric techniques, some very rapid isolated rotating stars were also investigated, opening a new window on the stellar rotation (van Belle et al 2001(van Belle et al , 2006Domiciano de Souza et al 2003;Aufdenberg et al 2006;Peterson et al 2006;Monnier et al 2007;Zhao et al 2009). In Che et al (2011) the predicted theoretical transition zone between radiative/convective envelopes (Claret 1998) was confirmed by using rapid rotators, some of them near the breakup velocities.…”
Section: Introductionmentioning
confidence: 73%
“…3 in Claret 2003). However, some discrepancies are present too, as such Che et al (2011), who studied the hot star α Leo and found β 1 = 0.75, significantly lower than the value predicted by von Zeipel's theorem (β 1 = 1.0). On the other hand, the detected scattering of the semi-empirical values of β 1 around the theoretical values of double-lined eclipsing binaries also demand a theoretical explanation.…”
Section: Introductionmentioning
confidence: 94%